PENINGKATAN HASIL BELAJAR PADA MATERI PENGIDENTIFIKASIAN JENIS- JENIS TANAH MELALUI PENDEKATAN KONTEKSTUAL PADA PESERTA DIDIK KELAS V SDN MAGERSARI SIDOARJO - Fajari, Akhmad Afif Al; Yasin, Fajar Nur (Jurnal Muassis Pendidikan Dasar, 2024)
This research aims to improve learning achievement on the material of identifying soil types through a contextual approach for class V students at SDN Magersari Sidoarjo. The method used is the classroom action research method, the research was conducted at SDN Magersari Sidoarjo. The subjects used in this research were class V with a total of 27 students consisting of 16 boys and 11 girls. The results of the research show that from cycle completeness, the pre-action activities obtained a class average score of 64.07 with classical completeness of 62%, increasing in cycle 11 to 72.59 with classical completeness of 70%. The average class score in cycle 2 was 81.85 with classical completeness of 81%. The conclusion of this research is that a contextual approach to the material on identifying class V soil types at SDN Magersari can improve student learning outcomes.